A study on acoustical analysis of laugh in children, adult females and adult males in different contexts - Reshmi Mohanan; Swetha G; Apala Gupta (Journal of All India Institute of Speech and Hearing, 2013)
Emotional key called laughter is expressions of happiness that may depend on conditions, situations and mood that are responsible for the different acoustic features, which vary because of glottal source and vocal tract. The study aimed to compare the variation of acoustic patterns of laugh between adult males, adult females and children in different contexts (tickle and humor). The study was carried out between 10 adult males (18-30 years), 10 adult females (18-30years) and 10 children (3-12 years) with no voice problem and have normal intelligence quotient to understand the humor. Recordings done in a sound treated room without any environmental disturbances and special attention taken for appropriate space for sitting arrangement and placement of microphone and laptop. Stimulus used to elicit laugh were tickle and video clips (i.e., funny videos for adults and Tom and Jerry clips for children) for humor. Results of the study found that in adult males, only f2 and f3 were the parameters that had a high level of significance (P<0.05) to differentiate between tickle and humor, while other parameters like f0, f1, pitch max, pitch min and intensity did not get affected in tickle and humor. In adult females, only f0 (P<0.05) varied in different laugh context (tickle and humor), but other parameters (f1, f2, f3, pitch max, Pitch min, Intensity) had no level of significance. In children f0, f1, f3, pitch max and intensity played a very important role to distinguish between tickle and humor and rest of the other parameters showed no difference. Children had highest mean formant frequencies secondary to adult females and were least in adult males for laughs elicited by tickle and humor. When tickle and humor were compared based on their mean values, tickle (1396) was higher than humor (1233). Thus various parameters extracted will help in forensic studies and can throw light on various emotional researches.